Expression of Melan-A in Depigmented Skin of Vitiligo Patients - Tjokorde Istri Nindya Vaniary; M. Yulianto Listiawan; Dwi Murtiastutik (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Vitiligo is an acquired and commonly found pigmentation disorder characterized by milky-white patches on the skin, hair, and mucosa due to melanocyte damage. The cause of vitiligo is still unclear. A study proves that cell-mediated immunity plays a role in the pathogenesis of vitiligo. Melan-A is a melanoma-related antigen that is recognized by autologous cytotoxic T cells and one of the critical markers for detecting melanocytes. Objective: To evaluate the expression of Melan-A in depigmented lesions of vitiligo patients. Methods: A descriptive study aimed to describe the expression of Melan-A in the depigmented skin of vitiligo patients at the Dermatovenerology Outpatient Clinic Cosmetic Division of Academic General Hospital Dr. Soetomo Surabaya. Eleven study subjects were selected through a sequence of selection. Results: Melan-A expression in the depigmented skin of vitiligo patients was lower than the average. This result was found in 6 (54.55%) out of 11 patients. Conclusion: Melan-A expressions on depigmented skins of vitiligo patients are generally below the average value; therefore, adequate intervention is needed to increase the Melan-A expression.